Law on State enterprises - The National Assembly (2003)
This Law prescribes the prescription of the establishment, reorganization, dissolution, ownership conversion, organization of management and operation of State companies; Regulation of relationships between the owner being the State and the representative of the State's contributed capital portions at enterprises where the State owns the entire charter capital or enterprises where the State holds dominant shares or contributed capital